Effectiveness of Angel Salazar memorial general hospital (ASMGH) in delivering health service as perceived by the public - Abiera, Maria Donna H.; Capistrano, Geralyn T. (1998)
This research paper was an attempt to identify and analyze the factor affecting the effectiveness of Angel Salazar memorial General Hospital (ASMGH) in San Jose, Antique, in delivering health service as perceived by the public. The respondents of the study were customers or patients of ASMGH, who have availed of its service either as in-patients or out-patients. The hospital personnel, the Chief of the hospital and the Governor of the Province of Antique were also the subjects of this research. The method used in this study was the descriptive evaluative method. Survey questionnaires and interview method made by the researchers were used in order to seek answers to the objectives of the study which were: 1) to identify the important factors in delivering quality health service oas perceived by the public ; 2) to discuss the importance of each identified factors; 3) to find out the present state of hospital operations in terms of personnel management which includes hiring and screening policies, leadership and motivational factors; 4) to determine the level of satisfaction and priorities of customers/patients in terms of health services offered by ASMGH; 5) t determine the perception of hospital personnel and customers/patients regarding the adequacy,completeness and appropriateness of hospital facilities and equipment as well as the cleanliness and sanitation of environment; 6) to determine the level of financial support extended by the government to the hospital, and 7) to formulate recommendations for the improvement of the present operations of ASMGH. In the analysis of the findings of the study, the descriptive statistical tool was used. Frequency distribution or the use of simple percentages were employed in the description of the results of the survey questionnaires. The Kendall Concordance Coefficient was also used to determine the degree of agreement on customer's/patients' responses on their priorities in availing health service. The Chi-square test was also utilized to determine the significant relationships of the null hypothese. The descriptive-evaluative method was made on date which could not be quantified including the responses during the interview.The general findings of the study were described in terms of frequency distribution. The inferential data were described in terms of frequency distribution. The inferential data were analyzed using the Chi-square and Kendall Concordance Coeffecientfor ranking. The significance level for inferential tests was set at .05. The findings of the resent investigation included the following : 1) the elements of management process and human resources, technology, hospital environment and financial resources were vital for an effectivehealth service, 2) the majority of hospital personnel were able to apply through word of mouth and mostly all employees have undergone various orientations such as organizational culture, work ethics, patient care, organization mission and vision and employee expectations,3) the motivational factors of salary and benefits, training and development, performance and evaluation, and working environment were employed by the hospital, 4) the level of satisfaction of hospital employees in terms of salaries, benefits, privileges, working environment, job, and training and development were inadequate. 5) the perceptions of customers/patients reagrding facilities and equipment were inadequate, incomplete and appropriate, 6) the personnel's opinion regarding facilities and equipment were inadequate., 7) the personnel's assessment regarding the completeness and advancement of facilities and equipment were good, 8) the perceptions of customers/patients regarding the present conditions of hospital environment were poor, 9) the personnels assessment regarding cleanliness and sanitation of hospital environment were good, 10) the customers/patients were not satisfied regarding the attitudes, dealings and services of hospital personnel, 11) the customers'/patients' priorities in availing health service of the hospital were based on the following :1) provide modern, advance and complete facilities and equipment; (2) improve and maintain cleanliness and sanitations; (3) conduct seminars to hospital personnel regarding patients relations/values; and (4) ask for government financial assistance; 15) amongthe suggestions of hospital personnel to improve hospital services were the following: (1) upgrade facilities, (2) hire additional staff, (3) maintain cleanliness and sanitation, (4) provide sufficient and adequate hospital supplies, and (5) provide additional funds; 16) the computed chi-square value of 4.49 is greater than the tabulated value which is 3.84 with a degree of freedom equals to 1 and a level of significance set of .05. This means that the null hypothesis of no significant relationship between customers'/patients' level of satisfaction on overall services/attitudes/dealings of hospital personnel and personnel's level of satisfaction in terms of happiness and contentment with job is rejected,17) the computed chi-square value of 1.53 is smaller than the tabulated value which is 3.84 with a degree of freedom equals to 1 and a level of significance set at .05. This means that the null hypothesis of no significant relationship between customers'/patients' level of satisfaction on overall services/attitudes/dealings of hospital personnel and personnel's level of satisfaction in terms of salaries and benefits is acepted, 18) the computed chi-square value of .68 is smaller than the tabulated value which is 3.84 with a degree of freedom equals to 1 and a level of significance set at .05. This means that the null hypothesis of no significant relationship between personnel's level of satisfaction in terms of salaries and benefits and level of satisfaction in terms of happiness and contentment with job is accepted.
Research Paper (BM 299-Research Methods and Applications). -- [Iloilo City] : UPV-CM, October 1998.